Online News Use Habits of University of Jordan Students - Al Subaihi , Suha S. (Dirasat: Human and Social Sciences, 2023)
Objectives: Young people's news consumption has evolved due to increased online news media and the shift to online education during the Covid-19 pandemic. This study investigates changes in news habits among Jordanian youth. Methods: The study is based on a quantitative survey of students (N=147) enrolled at the University of Jordan, Amman, Jordan, aged between 18 and 30 years, using voluntary response sampling. The survey questionnaire was conducted in order to explore their news consumption habits and media preferences, with a highlight on social media as a way to acquire and share news items. Results: The results provide that the vast majority of students (69.4%) are news consumers, although with different usage habits and consumption patterns. Nevertheless, the findings revealed that the internet is the most used path to get news, with news websites and social media platforms as the most preferred. The majority of surveyed students (74.2%) share news via social media, mostly with family members and close friends. Moreover, gender in this study was found to have a major influence on news type preferences. Sports news is the type of news that most male students in the sample were interested in following, whereas most female students were interested in following societal news. Conclusions: This study established that university students are followers of news, national and international, and that there is a rise in the importance of online news, particularly social media and non-mainstream news websites among young adults. Results suggest that young people are also news sharers.